The problem of managing patients with community-acquired pneumonia combined with COVID-19 in comorbid conditions (literature review) - Skorokhodova, N. O.; Fushtei, I. M.; Скороходова, Наталя Олегівна; Фуштей, Іван Михайлович (My University, 2024)
Background. The unprecedented in the history of mankind problem of COronaVIrus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2), having raised a huge number of fundamental questions about the pathogenesis of pneumonia. Aim. To analyse the features of community-acquired pneumonia in COVID-19, markers of inflammation, the impact of comorbidities, and the implications for improving diagnosis and treatment in patients with comorbidities according to the professional literature. Materials and Methods. We analyzed the literature on community-acquired pneumonia as-sociated with COVID-19 in comorbid conditions. The search for scientific information was car-ried out using the scientific databases Scopus, Pub Med, Web of Science, Google Scholar. Results. The analysis of the literature showed that the diagnosis of community-acquired pneu-monia in COVID-19 requires the use of modern polymerase chain reaction platforms to verify the SARS-CoV-2 virus, atypical bacterial pathogens, fungal flora and determine drug resistance. SARS-CoV-2 pneumonia is characterized by the development of radiological patterns that can only be detected by Computed Tomography (CT) of the chest. Digital software processing of CT images allows to determine the dynamics and stage of development of pneumonia in COVID-19, to assess the effectiveness of treatment and the presence of residual changes. Community-ac-quired pneumonia provokes the development of hypercoagulability, but the likelihood of deve-loping thrombosis in pneumonia with COVID-19 is much higher, which requires additional re-search and medical correction. Conclusions. The role of the outpatient stage of medical care is important in increasing patient adherence to timely diagnosis, treatment and prevention of chronic diseases, which can contribute to the benign course of community-acquired pneumonia in COVID-19 and reduces the risk of death.
Keywords: inflammatory markers; thrombosis; comorbidities; coronavirus disease